Gynura procumbens Ethanolic Extract Promotes Lymphocyte Activation and Regulatory T Cell Generation In Vitro - Dinia Rizqi Dwijayanti; Muhaimin Rifa'i (Journal of Tropical Life Science, 2015)
Immune system is a system of biological structures and processes within organism directed to protect against invaded pathogen. Cellular and humoral immune system mediated by immunocompetent cells such as CD4+ T cells, CD8+ T cells, CD4+CD25+ T cells, and B220 cells play important role for maintaining immunological surveillance. The purpose of this study was to determine the effect of ethanolic extract of G. procumbens leaves (EEGL) on the profile of CD4+ T cells, CD4+CD25+ T cells, and B220+ cells. Splenic cells were isolated from BALB/c mice and cultured in RPMI1640 medium in the presence of EEGL. After 4 days of incubation, cells were harvested, stained with antibodies and analyzed by flow cytometer. The data were analyzed by one-way ANOVA with α= 0.05 and Tukey test using SPSS 16.0 for windows. The results showed that the extract of G. procumbens could increase proliferation of CD4+CD62L T cell, CD4+CD25+T cells, and B220+ cells compared to the control. Here, we showed the biological effect of G. procumbensas medicinal herb with immunomodulatory activity andthe dose of 0.1 µg/ml and 1.0 µg/ml could promote T cell activation compared to the highest dose of 10 µg/ml. In terestingly, the dose of 10 µg/ml rather promote than inhibit B cell proliferation.